1997
DOI: 10.1007/s001010050399
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in intensive care medicine

Abstract: In more than 30 years of development of intensive care medicine (ICM), our specialty has acquired moral and ethical standpoints, although not without public pressure and discussions. Special commissions dealing, e.g., with brain death, terminal care, ethics of foregoing life-sustaining treatment in the critically ill, withholding or withdrawing mechanical ventilation, and other issues have been formed in a number of medical societies. International consensus conferences have helped to clarify some of the issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…The timing of such decisions includes the prehospital setting (outpatient, nursing home, palliative care, etc.) [136][137][138][139][140][141][142][143][144][145][146][147], at the time of arrival to the emergency room, upon hospital admission [148,149], during hospitalization [150][151][152][153], operating room [154][155][156], intensive care unit [157][158][159][160], or day of death [161]. One study of intentional ivermectin pesticide ingestion found that three patients developed respiratory failure but were not intubated because of a DNR order [162].…”
Section: Legal/policymentioning
confidence: 99%
“…The timing of such decisions includes the prehospital setting (outpatient, nursing home, palliative care, etc.) [136][137][138][139][140][141][142][143][144][145][146][147], at the time of arrival to the emergency room, upon hospital admission [148,149], during hospitalization [150][151][152][153], operating room [154][155][156], intensive care unit [157][158][159][160], or day of death [161]. One study of intentional ivermectin pesticide ingestion found that three patients developed respiratory failure but were not intubated because of a DNR order [162].…”
Section: Legal/policymentioning
confidence: 99%
“…http://dx.doi.org/10.1590/1983-80422022302535PT Ética do uso de escores prognósticos em unidade de terapia intensiva: revisão integrativa Quadro 3. Artigos que questionam o modelo de alocação de recursos baseado nos escores prognósticos Dos artigos classificados nessa categoria, apenas três discutem as implicações éticas relacionadas às escolhas médicas, que não seriam somente técnicas, mas também morais [53][54][55][56] . Os artigos dessa categoria classificam alguns dos escores prognósticos como injustos, como por exemplo: a possibilidade de o médico admitir apenas pacientes que tenham enfermidades que se relacionem com sua especialidade, bem como a idade dos pacientesindicador comum entre os escores, tal como o utilizado pelo Apache.…”
Section: Questionamento Dos Escores Como Pilar Para Triagemunclassified
“…Shows that, despite the prognostic scores, triage for ICU admission is based on another order of priorities, according to which the number of available beds is more significant "End-of-life decisions in Greek intensive care units: a multicenter cohort study" Ethics in the use of prognostic scores in intensive care units: an integrative review Title Year Main characteristic "Ten common questions (and their answers) on medical futility" 58 2014 Regarding prognostic scores, it understands that there is no way to accurately determine the days of life of a patient and that such rigid data cannot be predictive of choice to continue or start important medical care "Predicting the future-big data, machine learning, and clinical medicine" Of the articles classified in this category, only three discuss the ethical implications related to medical choices, considered not only technical but also moral [53][54][55][56] . These studies classify some of the prognostic scores as unfair, such as: the physicians' possibility to admit only patients who have diseases related to their specialty, as well as the age of the patients-a common indicator among scores, such as APACHE.…”
Section: Year Main Characteristicmentioning
confidence: 99%